The monitoring of a former contamination caused by uranium mining in Licoměřice (the Czech Republic) - Krejčová, Anna; Audrlická Vavrušová, Lenka; Popková, Silvie (University of Pardubice, 2013)
The paper has been focused on the development of the former uranium mining site located in Licoměřice. The orthogonal time-of-flight inductively coupled plasma mass spectrometry was the method of the choice for the uranium determination in water samples. The analytical procedure for the determination of uranium in water using the oTOF-ICP-MS method was processed. The limit of detection for uranium was 0.009 μg l–1. Sixty seven samples taken from former mining sites and also from non-mining sites were analysed. Emission limits for uranium were specified in the resolution of the State office for nuclear safety, Prague No. 9156/4.3/00 agreed on 17th July 2000. The recording level of uranium emission limits was exceeded in the case of ten water samples, the controlling level of emission limits for five water samples, and the emergency lever of emission limits for four water samples. The highest concentration of uranium has been found in the samples taken in the mining water treatment area in Licoměřice. According to the Government resolution No. 23/2011, Appendix 3 (the indicators and values of permissible pollution of surface water and wastewater, requisites of permit to discharge wastewater into surface water and sewerage systems and about sensitive areas) the imission limit allowed for the contamination with uranium in surface water is 40 μg l–1. This value has been exceeded in four samples. As the uranium concentration in the downstream flow has been found under the imission limit and shown the lowering tendency during the mining water treatment process, the recultivation and remedial measures taken by the state owned company DIAMO in former mining site Licoměřice can be considered as efficient.